2023
DOI: 10.3389/fped.2023.1167871
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of multisystem inflammatory syndrome in children: A multicenter, retrospective, observational cohort study in Mexico

Abstract: IntroductionMultisystem inflammatory syndrome in children associated with coronavirus disease 2019 (MIS-C), a novel hyperinflammatory condition secondary to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, is associated with severe outcomes such as coronary artery aneurysm and death.MethodsThis multicenter, retrospective, observational cohort study including eight centers in Mexico, aimed to describe the clinical characteristics and outcomes of patients with MIS-C. Patient data were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…From 2009 to 2018, the annual number of publications gradually increased, indicating that more scholars were paying attention to the importance of IVIG resistance research. From 2019 to 2022, the number of publications increased significantly, which may have been due to the COVID‐19 pandemic, when a large number of children had KD‐like symptoms 26,27 . What is more, we noticed a rapid increase in the number of publications and citations in 2019, during which a phase III clinical trial in Japan confirmed that initial treatment with IVIG and cyclosporine (CSA) improved the prognosis of coronary artery injury 28 …”
Section: Discussionmentioning
confidence: 88%
“…From 2009 to 2018, the annual number of publications gradually increased, indicating that more scholars were paying attention to the importance of IVIG resistance research. From 2019 to 2022, the number of publications increased significantly, which may have been due to the COVID‐19 pandemic, when a large number of children had KD‐like symptoms 26,27 . What is more, we noticed a rapid increase in the number of publications and citations in 2019, during which a phase III clinical trial in Japan confirmed that initial treatment with IVIG and cyclosporine (CSA) improved the prognosis of coronary artery injury 28 …”
Section: Discussionmentioning
confidence: 88%
“…Diagnostic criteria for benign acute childhood myositis was children presenting with sudden gait-related abnormalities or refusal to bear weight after a viral illness, neurologic findings are usually normal and creatinine kinase level is elevated, with conservative treatment measures, the condition usually resolves spontaneously within a week and without residual sequelae ( 12 ). Patient files were reviewed to identify cases of multisystem inflammatory syndrome in children (MIS-C) based on relevant literature references ( 13 , 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…Another study found no difference in mortality between nonsevere (0%) versus severe (0.96%) disease among infants admitted to the hospital.10) Comorbidities may be associated with mortality, but it must also be considered that, in the face of congenital anomalies and other significant comorbidities, the cause of death may not always be truly ascribed to SARS-CoV-2 [ 23 , 32 , 111 ]. Deaths among children with MIS-C or MIS-N presentations have been published [ 9 , 46 , 49 , 112 , 113 ].…”
Section: Covid-19 Among Infantsmentioning
confidence: 99%
“…23,32,111) Deaths among children with MIS-C or MIS-N presentations have been published. 9,46,49,112,113) Autopsy studies of deceased infants are meager, and most accumulation of COVID-19-related autopsy information stems from the findings among deceased adults. 114,115) Reviews for pediatric autopsy tend to focus on older children, and the proportionate number of infants aged <1 year has been <50%.…”
Section: Potential For Infant Mortalitymentioning
confidence: 99%